Peran Strategis Ulama dalam Pengembangan Ekonomi Syariah - Muhammad Yasir Nasution (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2014)
The Islamic scholars and  its institutions have an important role in strengthening the knowledge and horizons in  Mu'amalat Fiqh and  Syari’ah economics so such an important role can be effectively implemented. However, in this case the most important things  is a commitment; firstly  need to be built  a strong commitment among the Islamic scholars and the religious teaching institutions to develop syari’ah economics, for the welfare of the people and the nation.